2018
DOI: 10.1021/acs.biochem.8b00391
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the C481S Ibrutinib-Resistance Mutation in Bruton’s Tyrosine Kinase Using PROTAC-Mediated Degradation

Abstract: Inhibition of Bruton's tyrosine kinase (BTK) with the irreversible inhibitor ibrutinib has emerged as a transformative treatment option for patients with chronic lymphocytic leukemia (CLL) and other B-cell malignancies, yet >80% of CLL patients develop resistance due to a cysteine to serine mutation at the site covalently bound by ibrutinib (C481S). Currently, an effective treatment option for C481S patients exhibiting relapse to ibrutinib does not exist, and these patients have poor outcomes. To address this,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
282
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(290 citation statements)
references
References 63 publications
(118 reference statements)
6
282
0
2
Order By: Relevance
“…Accordingly, development of VHL-and CRBN-recruiting PROTACs based on a promiscuous kinase inhibitor ferotinib demonstrated that the degradation profiles of the two PROTACs were not identical, and that there was no correlation between the binding affinity of either PROTAC to the kinases and the extent of PROTAC-induced degradation of the kinases. 44) Thus, the suitable combination of an E3 ligase ligand and a target ligand is critically important to develop a potent degrader. In this point of view, it is important to identify a novel small molecule that recruits another E3 ubiquitin ligase to the target protein appropriately.…”
Section: Prospect Of Sniper(abl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, development of VHL-and CRBN-recruiting PROTACs based on a promiscuous kinase inhibitor ferotinib demonstrated that the degradation profiles of the two PROTACs were not identical, and that there was no correlation between the binding affinity of either PROTAC to the kinases and the extent of PROTAC-induced degradation of the kinases. 44) Thus, the suitable combination of an E3 ligase ligand and a target ligand is critically important to develop a potent degrader. In this point of view, it is important to identify a novel small molecule that recruits another E3 ubiquitin ligase to the target protein appropriately.…”
Section: Prospect Of Sniper(abl)mentioning
confidence: 99%
“…(PROTACs). [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] SNIPERs and PROTACs are chimeric molecules composed of two different ligands connected by a linker; one ligand is for the target protein and the other is for E3 ubiquitin ligases. Accordingly, these molecules are expected to crosslink the target protein and E3 ubiquitin ligases in cells, resulting in ubiquitylation and subsequent degradation of the target protein via the ubiquitin-proteasome system (UPS) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At almost the same time, the Crews group reported another BTK PROTAC, MT-802, derived from ibrutinib 168 (Fig. 13).…”
Section: Brd9 and Brd7mentioning
confidence: 93%
“…Targeted protein degradation induced by small molecules is an emerging strategy in chemical biology and drug discovery . These molecules, often called proteolysis targeting chimeras (PROTACs), have potential therapeutic advantages over typical inhibitors, and the first examples of this technology have recently entered clinical trials . PROTACs are heterobifunctional molecules that bind to a POI and an E3 ligase protein simultaneously (Figure A).…”
Section: Covalent Inducers Of Protein Degradationmentioning
confidence: 99%